Dapagliflozin Ameliorates Diabetic Kidney Disease via Upregulating Crry and Alleviating Complement Over-activation in db/db Mice - Chang, Dong-Yuan; Li, Xiao-Qian; Chen, Min; Zhao, Ming-Hui (Frontiers in Pharmacology, 2021)
Sodium-glucose cotransporter 2(SGLT2) inhibitors show prominent renal protective effect in diabetic kidney disease (DKD), anti-inflammatory effect being one of its key mechanisms. Over-activation of the complement system, a crucial part of innate immunity, plays an important role in DKD. We aimed to investigate the effect of SGLT2 inhibitors on alleviating complement over-activation in DKD. Db/db mice were randomly divided into two groups, with 7 mice in each group treated with dapagliflozin and vehicle respectively, and 7 mice in m/m mice group. Laboratory and renal pathological parameters were evaluated. Mouse proximal tubular epithelial cells (MPTECs) were cultured and treated with high glucose. Dapagliflozin and dimethyloxallyl glycine (DMOG) were added as conditional treatment. Dapagliflozin-treated db/db mice showed significantly lower urinary albumin than vehicle-treated ones. Besides typical glomerular and tubulointerstitial injury, both C3b and membrane attack complex (MAC) depositions were significantly attenuated in dapagliflozin-treated db/db mice. The expression of complement receptor type 1-related protein y (Crry), a key complement regulator which inhibits complement over-activation, was significantly upregulated by dapagliflozin. Dapagliflozin-mediated Crry upregulation was associated with inhibition of HIF-1α accumulation under high glucose. When HIF-1α expression was stabilized by DMOG, the protective effect of dapagliflozin via upregulating Crry was blocked. In conclusion, dapagliflozin could attenuate complement over-activation in diabetic mice via upregulating Crry, which is associated with the suppression of HIF-1α accumulation in MPTECs.